2014
DOI: 10.1080/19420676.2014.954259
|View full text |Cite
|
Sign up to set email alerts
|

What's Holding Back Social Entrepreneurship? Removing the Impediments to Theoretical Advancement

Abstract: This article summarizes four contributions that were presented in a professional development workshop at the 2013 Academy of Management conference. The goal of the workshop was to discuss impediments to the theoretical advancement of social entrepreneurship. This paper's first two contributors discuss assumptions and boundaries of social entrepreneurship, exhibiting contrasting views of whether theory should be aggregated or disaggregated. The other two scholars focus on specific topics that advance social ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
7
0
6
Order By: Relevance
“…The probability value of this study was lower than 0.050 (0.000) which means H4, H5 is accepted. This finding support by Martín & Martín & Cuervo-Arango (2016) and Mueller et al (2015) who stated that factors like excessive official formalities, rigid procedures, excessive administrative hurdles and unreasonable delay to obtain governments assistance are major obstacles in determining the intention on social entrepreneurship among the youth generation. Newey (2018) added that factors like difficulty in obtaining finance, government regulations, adequate business support, and tax regulations are perceived to be major barriers to social entrepreneurship.…”
Section: Spearman's Correlationsupporting
confidence: 61%
See 1 more Smart Citation
“…The probability value of this study was lower than 0.050 (0.000) which means H4, H5 is accepted. This finding support by Martín & Martín & Cuervo-Arango (2016) and Mueller et al (2015) who stated that factors like excessive official formalities, rigid procedures, excessive administrative hurdles and unreasonable delay to obtain governments assistance are major obstacles in determining the intention on social entrepreneurship among the youth generation. Newey (2018) added that factors like difficulty in obtaining finance, government regulations, adequate business support, and tax regulations are perceived to be major barriers to social entrepreneurship.…”
Section: Spearman's Correlationsupporting
confidence: 61%
“…Instead of personal and shareholder's wealth gain, the underlying cause of social entrepreneurship is to create social value, and that action is characterized by innovation, or the institution of something new rather than simply the return of existing enterprises or practices. According to Mueller et al (2015), the government acknowledges its problem-solving nature and stimulates social entrepreneurship due to its innovation. Phillips et al (2015) analyzed the literature to discover the association between social innovation and social entrepreneurship and concluded that both of them aim to quest after solving societal problems.…”
Section: Introductionmentioning
confidence: 99%
“…Social entrepreneurs take it on themselves to develop innovative solutions for such societal challenges (Dees 2007), in particular those that governments, for-profit and non-profit organizations fail to address (properly) (Sud, VanSandt, and Baugous 2009). This problem-solving role in society is recognized by governments, who therefore stimulate social entrepreneurship and innovation, especially in times of general retrenchment (Mueller et al 2015;Shaw and de Bruin 2013). Supporting organizations such as Ashoka and the Skoll foundation have also created platforms for social entrepreneurship to stimulate their problem-solving role in society.…”
Section: Introductionmentioning
confidence: 99%
“…This adds substantially to our understanding of the complexity and ambiguity of corporate values in relation to internal organizational dynamics and potentially ensuing scandals, that is, Mertonian innovation. Second, by studying the relation between corporate values and scandals, we contribute to a more fine‐grained understanding of why in principle desirable corporate values—such as integrity or customer focus—do not prevent undesired behaviors focused on short‐term economic value creation but possibly leading to economic and social value destruction in the long run (also see Mueller et al, ). Third, by comparing characteristics of the firms in our sample, we explore the possible effects of such characteristics on the selection and outcomes of corporate values.…”
Section: Introductionmentioning
confidence: 99%